Anthracosis in a Baboon From a Zoological Garden. A Case Report - Flavia Ruxanda; Adrian Florin Gal; Bianca Boşca; Bianca Alexandra Matosz; Vasile Rus; Cristian Raţiu; Viorel Miclăuş (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Veterinary Medicine, 2016)
Anthracosis is a disease encountered in both humans and animals. The present study was conducted on a baboon from a zoological garden, which died of natural causes. During morphopathological examination, we observed pulmonary anthracosis, with coal particles in both macrophages’ cytoplasm and free in septa, interstitium and pleura. The pulmonary anthracosis was moderate, thus the structural and fuctional changes were minimal and the disease evolved without any clinical manifestation.